PENGARUH REGULASI NORTH AMERICA FREE TRADE AREA (NAFTA) TERHADAP EKSPOR PRODUK PERTANIAN MEKSIKO KE KANADA DAN AMERIKA SERIKAT (TAHUN 2004-2009) - Didiek Firgiawan Putra; Saiman Pakpahan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This paper discusses the differences before the abolition of trade barriers as a whole and after the holding of the elimination of tariff barriers as a whole since the merger of Mexico into NAFTA. This study is compiled from some resourse and references including book, newspaper, magazines and some site in internet. It is qualitative method by using the theory of international organization of Michael Hass. With the issuance of Chapter 7 of the regulation of agricultural trade regulation and enforcement of the FTA in total, helping boost agricultural exports products throughout the NAFTA member countries, especially Mexico. This research regulations issued by the NAFTA on agriculture have a positive impact on agriculture in Mexico on the mark with the growing number of Mexican farm exports in the current holding of tariff elimination.Key words : Regional Organizations, International Political Economy, NAFTA, Mexico.